THE BRADYKINESIA–AKINESIA INCOORDINATION TEST: A SIMPLE OBJECTIVE TEST IN MULTIPLE SCLEROSIS. Issue 11 (9th October 2013) - Hadavi, Shahrzad; Shribman, Sam; Nagy, Anna; Acharya, Shami; Fearnley, Julian; Dobson, Ruth; Lees, Andrew; Giovannoni, Gavin; Noyce, Alastair
Abstract : Background: The Bradykinesia Akinesia Incoordination (BRAIN) test is an online computer keyboard–tapping task based on the alternate finger tap test. It has previously been used to measure upper limb motor function in Parkinson's disease (PD). Multiple Sclerosis (MS) is an autoimmune demyelinating disorder with a wide clinical spectrum, within which pyramidal motor impairment is encountered frequently. There is a need for simple objective measures of upper limb function in clinical studies of symptomatic and disease–modifying treatment in MS. We therefore set out to evaluate whether the BRAIN test would be a suitable objective test of upper limb motor impairment in MS patients. Methods: The BRAIN test records the following parameters: kinesia score (KS30), number of key taps in 30 seconds; akinesia time (AT30), mean dwell time on each key in milliseconds; dysmetria score (DS30), a weighted index using the number of incorrectly hit keys scored in a target fashion; and incoordination score (IS30), the variance of the time interval between keystrokes. The study was undertaken in 32 MS patients (5 primary progressive, 19 secondary progressive, and 8 relapsing–remitting). These data were compared to that from 53 PD patients and 86 non–neurological controls. Participants were recruited from outpatient departments at the Royal London Hospital and the National Hospital for Neurology and Neurosurgery. All participants submitted informed consent. Mean KS30 and median AT30, DS30 and IS30 were compared between groups using the unpaired t–test for parametric data and the Mann Whitney U test for non–parametric data. Furthermore, in MS patients, KS30 and AT30 were correlated against Expanded Disability Status Scale (EDSS), a validated method of quantifying disability, and 9–Hole Peg Test (9–HPT), a test of upper limb function in MS. Correlations were undertaken using Pearson's test and Spearman's rank test as necessary. Results: Mean KS30 scores in PD and MS were similar (46.1 versus 45.7 taps respectively, p=0.88) and were significantly different when compared to controls (63.3 taps, p<0.0001). There was a significant difference between median AT30 in PD and MS (139.5 ms versus 108 ms, p=0.0014) but no difference between MS and controls (108 ms versus 97.5 ms, p=0.16). Median IS30 scores in PD and MS were different (21763 versus 9524 respectively, p=0.004), as were DS30 scores (1.05 versus 1.0 respectively, p=0.003). In MS patients, KS30 correlated strongly with EDSS (KS30 r=–0.59, p=0.0004) and 9–HPT (KS30 r=–0.57, p=0.0006). Other parameters did not show a significant correlation with EDSS and 9–HPT. Conclusion: The BRAIN test is a widely–available, objective test of upper limb motor function in neurological disease and can be use in the outpatient clinic, home and in clinical trials. Tapping speed is reduced in MS patients when compared to healthy controls and by a similar extent to that seen in PD. MS patients do not have prolonged dwell time when pressing keys, which is a feature of the PD patient group and perhaps extra–pyramidal slowing. This potential for the BRAIN test in differentiating pyramidal from extra–pyramidal motor dysfunction requires further study.